2014
DOI: 10.1007/s12665-014-3906-1
|View full text |Cite
|
Sign up to set email alerts
|

A 850-year record climate and vegetation changes in East Siberia (Russia), inferred from geochemical and biological proxies of lake sediments

Abstract: East Siberia is very sensitive to moisture regimes because it is located in a margin area, where moisture from the North Atlantic is strongly depleted, and the penetration of the East Asian monsoon is weak and rare. In winter months, the Siberian anticyclone strongly blocks and reduces the external influences on the region. The high latitude of the study area at 52°N is probably sensitive to variation in insolation and solar activity. We analysed a 42-cm-long sediment record from Lake Mountain located in East … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 109 publications
0
6
0
Order By: Relevance
“…These diatoms are known in oligotrophic lakes of Siberia, Mongolia, North America, Europe and Miocene-Holocene (Genkal et al, 2011). Currently, the diatom species often occur in the mountain lakes around Lake Baikal (Fedotov et al, 2015;Vorobyeva et al, 2015). In general, we assume that climate was most likely warm and humid in this part of Eurasia at 4.5-3.5 ka BP.…”
Section: Resultsmentioning
confidence: 99%
“…These diatoms are known in oligotrophic lakes of Siberia, Mongolia, North America, Europe and Miocene-Holocene (Genkal et al, 2011). Currently, the diatom species often occur in the mountain lakes around Lake Baikal (Fedotov et al, 2015;Vorobyeva et al, 2015). In general, we assume that climate was most likely warm and humid in this part of Eurasia at 4.5-3.5 ka BP.…”
Section: Resultsmentioning
confidence: 99%
“…According to many reconstructions of global surface temperatures for the Northern Hemisphere, a transition from the Little Ice Age to the Recent Warming was characterized by a sharp increase in the annual temperature that occurred ca. 1850 to 1860 [28][29][30]. However, records from East Siberia revealed that significant changes in climate parameters, vegetation, and lake bio-productivity were not intense until 1900 [30].…”
Section: Isotopic Composition In 1991 1992 and 2021mentioning
confidence: 99%
“…Molybdenum Incoherent/coherent ratio (Inc/coh) approximates the average matrix composition of atomic numbers and was used to estimate organic matter content in sediment archives (Croudace and Rothwell, 2015;Field et al, 2018;Woodward and Gadd, 2019;Woodward et al, 2018). Br was used as another indicator for organic rich sediments (Croudace and Rothwell, 2015;Fedotov et al, 2015;Ziegler et al, 2008).…”
Section: Geochemistrymentioning
confidence: 99%